RAS and BRAF mutations in cell‐free DNA are predictive for outcome of cetuximab monotherapy in patients with tissue‐tested RAS wild‐type advanced colorectal cancer. Issue 11 (30th September 2019) - van Helden, Erik J.; Angus, Lindsay; Menke‐van der Houven van Oordt, C. Willemien; Heideman, Daniëlle A. M.; Boon, Eline; van Es, Suzanne C.; Radema, Sandra A.; van Herpen, Carla M. L.; de Groot, Derk Jan A.; de Vries, Elisabeth G. E.; Jansen, Maurice P. H. M.; Sleijfer, Stefan; et al.
Abstract : In metastatic colorectal cancer, RAS and BRAF mutations cause resistance to anti‐EGFR therapies, such as cetuximab. Heterogeneity in RAS and BRAF mutations might explain nonresponse in a subset of patients receiving cetuximab. Analyzing mutations in plasma‐derived circulating tumor DNA (ctDNA) could provide a more comprehensive overview of the mutational landscape as compared to analyses of primary and/or metastatic tumor tissue. Therefore, this prospective multicenter study followed 34 patients with metastatic colorectal cancer who were tissue‐tested as RAS wild‐type (exons 2–4) during routine work‐up and received third‐line cetuximab monotherapy. BRAF mutation status was also tested but did not exclude patients from therapy. At baseline and upon disease progression, cell‐free DNA (cfDNA) was isolated for targeted next‐generation sequencing (NGS). At 8 weeks, we determined that patients had benefited from treatment. NGS of cfDNA identified three patients with RAS mutations not detected in tumor tissue during routine work‐up. Another six patients had a BRAF or rare RAS mutation in ctDNA and/or tumor tissue. Relative to patients without mutations in RAS/BRAF, patients with mutations at baseline had shorter progression‐free survival [1.8 versus 4.9 months ( P  < 0.001)] and overall survival [3.1 versus 9.4 months ( P  = 0.001)]. In patients with clinical benefit (progressive disease after 8 weeks), ctDNA testing revealed previously undetected mutations in RAS/BRAF (71%) and EGFR (47%), which often emerged polyclonally. Our results indicate that baseline NGS of ctDNA can identify additional RAS mutation carriers, which could improve patient selection for anti‐EGFR therapies. Acquired resistance, in patients with initial treatment benefit, is mainly explained by polyclonal emergence of RAS, BRAF, and EGFR mutations in ctDNA. Abstract : Next‐generation sequencing (NGS) of cell‐free DNA (cfDNA) in patients with tissue‐tested RAS wild‐type mCRC can identify additional RAS mutation carriers. The majority of patients with clinical benefit from cetuximab therapy acquire multiple mutations in RAS, BRAF, and EGFR . Hence, cfDNA analysis is a promising tool to optimize patient selection for cetuximab therapy and is a minimally invasive method to understand mechanisms accounting for resistance.